Implementation of children kinesthetic intelligence development activities in kindergarten - Shinta Safenia Anisah; Nurhafizah Nurhafizah; Rivda Yetti (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2018)
The purpose of this study was to plan, implement, and evaluate the activities carried out by the teacher in developing the kinesthetic intelligence of children in the first kindergarten of the Padang governor’s office. The method used in this study is descriptive with a qualitative approach. Data collection techniques in this study were carried out through observation, interviews, and dokumentation. The data analysis techniques of data in this study using triangulation techniques.The results of this study indicate that the implementation of the kinesthetic intelligence development activities of children in the first kindergarten of the Padang governor’s office has been maximazed. First, seen from the semester program made by the teacher, the weekly learning implementation plan (RPPM), the plan of implementing daily learning (RPPH). Second, the implementation of the methods used varies, including direct practice methods, demonstration method, and methods of assigning assignments. Third, evaluations used are observation, performance and anecdotal records. It can be concluded that the planning, implementation, and evaluation of teachers can develop children’s kinesthetic intelligence and the achievements obtained include the runner up of the plate dance competition in the city of Padang, Batok dance, movements and songs etc.